Advances in Medical Education
XII, 820 p.
Keywords: About 550 registrants from 51 different countries attended the Seventh Ottawa Conference on Medical Education and Assessment in Maastricht. We received 525 abstracts for the conference, divided in thematic poster sessions and platform presentations. Organising the conference was an honour and we tried to meet the high standards of a friendly and relaxed atmosphere which has characterized previous Ottawa conferences. During and after the conference about 250 papers were submitted for publication in the conference proceedings, leaving us little time for a post-conference depression. Despite the large number of papers, the editors have attempted to review and edit the papers as care fully as possible. Occasionally, however, correspondence exceeded reasonable deadlines, preventing careful editing of a small number of the papers. Although we felt that our editorial task was not quite finished, we nevertheless decided to include these papers. We thank the many authors for their enthusiastic and prompt response to - occasionally tedious - editorial suggestions and requests. We are sure that this collective effort has resulted in a book that will make an important contribution to the field of medical education. The editors want to thank Jocelyn Flippo-Berger whose expertise with desk top publishing and perseverance was a great help.